Hypoxia-Related Hormonal Appetite Modulation in Humans during Rest and Exercise: Mini Review - Debevec, Tadej (Frontiers in Physiology, 2017)
Obesity is associated with numerous chronic ailments and represents one of the major health and economic issues in the modernized societies. Accordingly, there is an obvious need for novel treatment approaches. Recently, based on the reports of reduced appetite and subsequent weight loss following high-altitude sojourns, exposure to hypoxia has been proposed as a viable weight-reduction strategy. While altitude-related appetite modulation is complex and not entirely clear, hypoxia-induced alterations in hormonal appetite modulation might be among the key underlying mechanisms. The present paper summarizes the up-to-date research on hypoxia/altitude-induced changes in the gut and adipose tissue derived peptides related to appetite regulation. Orexigenic hormone ghrelin and anorexigenic peptides leptin, glucagon-like peptide-1, peptide YY and cholecystokinin have to-date been investigated as potential modulators of hypoxia-driven appetite alterations. Current evidence suggests that hypoxia can, especially acutely, lead to decreased appetite, most probably via reduction of acylated ghrelin concentration. Hypoxia-related short and long-term changes in other hormonal markers are more unclear although hypoxia seems to importantly modulate leptin levels, especially following prolonged hypoxic exposures. Limited evidence also suggests that different activity levels during exposures to hypoxia do not additively affect hormonal appetite markers. Although very few studies have been performed in obese/overweight individuals, the available data indicate that hypoxia/altitude exposures do not seem to differentially affect appetite regulation via hormonal pathways in this cohort. Given the lack of experimental data, future well-controlled acute and prolonged studies are warranted to expand our understanding of hypoxia-induced hormonal appetite modulation and its kinetics in health and disease.